DEVELOPING STUDENTS ABILITY TO WRITE A REPORT GENRE THROUGH THEMATIC PROGRESSION APPROACH (Action Research in the English Department, Faculty of Education and Teacher Training, Tidar University of Magelang) - Ikaningrum, Rini Estiyowati (Majalah Transformatika, 2009)
Teaching writing is not as easy as we think. The lecturer needs a certain way to teach writing, especially in the university level. The students ability in writing a text type especially a report depends on how they express their ideas. That is why the writer applies thematic progression Â as the approach in teaching report genre. The subject of this research is the thirdÂ semester students of the English Department, Faculty of Education and Teacher Training, Tidar University of Magelang which take writing 2 subject in the afternoon class. There Â are Â two Â instruments Â of Â this Â research;Â Â they Â are Â students paragraphÂ Â in about Â a Â hundred Â words Â and Â questionnaire Â (closedÂended questions that is questions on questionnaire that limit possible responses by providing specific choices or option yes or no). The first instrument (students paragraphs) and the second instrument (questionnaire) will be analyzed quantitatively. The students paragraphs were analyzed according to the rubric scoring that refers to analytic scoring. In this action research the writer applies three things; they are pre-test, test in cycle I and post-test in cycle 2. After analyzing students writing, it can be concluded that the use of thematic progression is really needed in teaching writing. It proved that the mean score of each cycle is slowly increased In .the pre-test, students just write a report paragraphÂ without knowing how to develop their ideas. In cycle 1, students get a new way in writing a report paragraph by using thematic progression. While in cycle 2, the students are trained in applying thematic progression. Besides, studentsâ motivation and seriousness in learning writing improve. They have good encouragement after getting the treatment. Key Word: ability, theme, rheme, thematic progression, reportÂ